Україна — Туреччина: грані співробітництва - Біляєва, С.О.; Кулаковська, Л.В.; Фіалко, О.Є. (Археологія і давня історія України, 2019)
Співробітництво України і Туреччини наприкінці ХХ — на початку ХХІ ст. в галузі археології
османських пам'яток розвивалося в різних напрямах: розкопки, польові та наукові розвідки, видання наукових праць, виставки, створення Історико-культурної асоціації «Україна — Туреччина», Міжнародні наукові конференції. The formation of the scientific cooperation of Ukraine
and Turkey began from the beginning of independence
state, after crushing of Soviet ideological system. From
1989. the archaeological investigations of historical
center of Ochakiv (Mikolayiv region) begin by expedition
of the Institute of archaeology of NAN of Ukraine. The
study of new collection, which include numerous artefacts of Turkish culture needed with consultations with
Turkish archaeologists. Due to help of the Ambassador of Turkey in Ukraine Acar Germen, the first international
contacts were established and in 1997—1998. first project in Ochakiv provided under the chief of prof. B. Ersoy
from Turkish side. In 1999 began joint the excavation in Akkerman, which continue till 2006. The results
of expedition published in numerous books and articles. The next direction of cooperation were exhibitions, which
take place in Kiev and Izmir. In 2005. the historical and cultural association Ukraine-Turkey created, member of
which represented various fields of study: archaeology, history, literature and language. A very important place
take archaeological investigation of the Ottoman monuments on the territory of Ukraine, which allow to discover
new view on the history both of countries, reconstruction of integrations in the system of material culture.